THE EFFECT OF LEARNING METHODS ON COGNITIVE CAPABILITY OF SCIENCE CONCEPT IN EARLY CHILDREN EDUCATION AMBON CITY - Hermelina Abarua; Rosmaryn Tutupary (EDU SCIENCES JOURNAL, 2020)
This study aims (1) Knowing cognitive abilities in early childhood science concepts taught by experimental methods in Ambon City PAUD (2) Knowing cognitive abilities in early childhood science concepts taught by demonstration methods in Ambon City PAUD (3) Test the significant difference in effect between the use of experimental and demonstration methods on cognitive abilities of early childhood science concepts in Ambon City PAUD. The research was carried out at KB Mawar FKIP Unpatti and TK Ambon Training Advisors. The method used is a quasi-experimental design with pretest-posttest control group design. The population of this research is all students of KB Mawar FKIP Unpatti and TK Kindergarten Ambon Training. Sampling of this study was carried out using proportional random sampling technique which was carried out randomly in 2 classes, namely 20 people. Data was collected through an instrument of observation of the cognitive abilities of scientific concepts. The reliability of achievement motivation instruments is 0.89, the learning achievement test is 0.90. Data from this study were processed using the t test analysis technique for independent samples at a significance level of Î± = 0.05. This research concludes that First. The experimental group children in KB Mawar have the cognitive ability of science concepts using the experimental method showing very good activity with the lowest score of 28 and the highest score of 40 obtained an average price of 35.4 with a Median of 35.5 and Mode of 35. Second. Control group children have the cognitive ability of science concepts using the demonstration method shows that activities develop well with the lowest score of 24 and the highest score of 38 obtained an average price of 30.4 with a median of 30.5 and a mode of 31. Third. 3. There are differences in the average cognitive ability of science concepts of children aged 5-6 years between students taught by the experimental method and students taught by the demonstration method with the price of tcount = 2.78 while the table of degrees of freedom nâ‚ + nâ‚‚ - 2 = 18 at the significance level Î± = 0.05, 1, 73, then t> t table, this means that the difference in the two means is significant at the 0.05 level. It can be concluded that there are differences in the average cognitive abilities of early childhood science concepts in the experimental and control groups. Thus it can be concluded that there is an effect of learning methods on the cognitive abilities of scientific concepts of children aged 5-6 years in Ambon City PAUD